Invasive signal crayfish and native noble crayfish show trophic niche shrinkage in sympatry - Ercoli, Fabio; Ruokonen, Timo J.; Bláha, Martin; Kouba, Antonín; Buřič, Miloš; Veselý, Lukaš (Pensoft Publishers, 2025)
Studying the coexistence of native species and invasive species with similar functional traits, habitat usage, and feeding habits is crucial for understanding the dynamics of invasion and ecological changes in the invaded ecosystem. Due to competitive exclusion and often also dissemination of crayfish plague pathogen (Aphanomyces astaci, Schikora), North American crayfish represent a major threat to European native crayfish. Their co-occurrence is often only temporary, making studies investigating trophic ecology of native and non-native crayfish species rare. In this study, trophic niche and feeding ecology of European native noble crayfish Astacus astacus (Linnaeus, 1758) and North American signal crayfish Pacifastacus leniusculus (Dana, 1852) were compared between their sympatric and allopatric sites, in Křesánovský brook (Czech Republic), using carbon and nitrogen stable isotopes analysis. The results indicated a substantial change of trophic niche and diet of noble crayfish between allopatry and sympatry. In allopatry, both juvenile and adult noble crayfish exhibited a wider trophic niche width compared to juvenile and adult signal crayfish. However, in sympatry, where adult and juvenile noble crayfish coexisted with signal crayfish, their trophic niche width significantly narrowed and their diet shifted towards a more plant-based one. High degree of trophic niche overlap was observed between adults and juveniles in both species, particularly in sympatry rather than in allopatry. The substantial trophic niche overlap and dietary similarity between native noble crayfish and invasive signal crayfish in sympatry, make their long term coexistence on the invaded site unlikely.
Keywords: allopatry; coexistence; diet; invasive species; native species; niche ecology; stable isotopes